Evidence for feasibility of fetal trophoblastic cell‐based noninvasive prenatal testing. (2nd October 2016) - Breman, Amy M.; Chow, Jennifer C.; U'Ren, Lance; Normand, Elizabeth A.; Qdaisat, Sadeem; Zhao, Li; Henke, David M.; Chen, Rui; Shaw, Chad A.; Jackson, Laird; Yang, Yaping; Vossaert, Liesbeth; et al.
Abstract: Objective: The goal was to develop methods for detection of chromosomal and subchromosomal abnormalities in fetal cells in the mother's circulation at 10–16 weeks' gestation using analysis by array comparative genomic hybridization (CGH) and/or next‐generation sequencing (NGS). Method: Nucleated cells from 30 mL of blood collected at 10–16 weeks' gestation were separated from red cells by density fractionation and then immunostained to identify cytokeratin positive and CD45 negative trophoblasts. Individual cells were picked and subjected to whole genome amplification, genotyping, and analysis by array CGH and NGS. Results: Fetal cells were recovered from most samples as documented by Y chromosome PCR, short tandem repeat analysis, array CGH, and NGS including over 30 normal male cells, one 47, XXY cell from an affected fetus, one trisomy 18 cell from an affected fetus, nine cells from a trisomy 21 case, three normal cells and one trisomy 13 cell from a case with confined placental mosaicism, and two chromosome 15 deletion cells from a case known by CVS to have a 2.7 Mb de novo deletion. Conclusion: We believe that this is the first report of using array CGH and NGS whole genome sequencing to detect chromosomal abnormalities in fetal trophoblastic cells from maternal blood. © 2016 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Analysis of cell‐free DNA for noninvasive prenatal testing (NIPT) is widely practiced, and the frequency of amniocentesis and CVS has decreased. However, cell‐free NIPT is not adequate for detecting smaller deletions and duplications with high specificity, sensitivity, and positive predictive value. Although fetal nucleated red blood cells and trophoblastic cells are known to be present in the maternal circulation, it has not been possible to develop a reliable cytogenetic cell‐based form of NIPT. What does this study add? Fetal cytotrophoblasts were successfully recovered from maternal blood. Although a clinical test has not been validated, for the first time, the feasibility of using array comparative genomic hybridization and next generation sequencing to detect chromosomal and subchromosomal abnormalities is demonstrated. The results suggest the possibility of developing a cell‐based form of NIPT with ability to detect abnormalities with a similar accuracy as can currently be obtained with amniocentesis and CVS.